(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The publication reveals the stylistic resource of simple sentences, the structural-semantic features of which reflect the synesthetic nature of art architechtonic (on the example of works created by the native land writer Olesya Omelchenko). Typical synesthetic images used in the language system are characterized on theoretical level; the mechanism of synesthetic images foundation and functioning is analyzed; the aspect of creation of esthetic sensuality with the view of the tendency of esthetic knowledge in the development of synesthetic language images in Ukrainian literary tradition as a whole and in the literature of native land particularly is described. Paying attention that synesthesia is considered to be a system sign of esthetic sensuality and also causes a new approach to the investigation of the problem of sensuality the article covers practical realization of possibilities of associating different types of perception, the interrelation of feelings in the act of perception of both reality and work of art, the research of the structure of polymodal perception on the level of images studied, and also style-forming sign of idiostyle when in the only cognitive act the involvement of different types of associations is performed and is in its turn one of the tendencies of a new view on art potential of language units as a part of art images. Psycholinguistic interpretation in the contents of linguistic analysis of synesthetic images representing the art background of Olesya Omelchenko allows to isolate and characterize a proper sensor component (feelings); a sensor-emotional component (psychological signs of emotion / state; corporal signs of emotion / state (information of corporal feelings, which the person experiences in this or that state; exterior signs of emotion / state ( information about the situations in which the person has a certain internal experience). The formed contents of synesthetic language images make a stylistic resource of language system and also are the defining sign of formation of valuable dominant and esthetic imperative of the language personality reflecting the esthetics of the work of art.